2010
DOI: 10.1677/jme-09-0168
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mediators of Wnt signalling pathways by GnRH in gonadotropes

Abstract: The binding of GnRH to its receptor on pituitary gonadotropes leads to the targeting of a diverse array of signalling mediators. These mediators drive multiple signal transduction pathways, which in turn regulate a variety of cellular processes, including the biosynthesis and secretion of the gonadotropins LH and FSH. Advances in our understanding of the mechanisms and signalling pathways that are recruited to regulate gonadotrope function are continually being made. This review will focus on the recent demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The transcription of GnRH target genes is modulated by several factors, such as β-catenin [24], which activation, in turn, is itself dependent on a number of molecules including intracellular Ca 2+ and CREB. Although β-catenin activation acts as an enhancer of the Lhb gene transcription [55], and immunostaining has revealed its weak inhibition by Teverelix, all three antagonists had similar effects on GnRH-induced Lhb expression. These data highlight the potential of GnRH antagonists in exerting LiSS behavior at the early signaling level, in spite of the similar inhibition of gonadotropin production.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription of GnRH target genes is modulated by several factors, such as β-catenin [24], which activation, in turn, is itself dependent on a number of molecules including intracellular Ca 2+ and CREB. Although β-catenin activation acts as an enhancer of the Lhb gene transcription [55], and immunostaining has revealed its weak inhibition by Teverelix, all three antagonists had similar effects on GnRH-induced Lhb expression. These data highlight the potential of GnRH antagonists in exerting LiSS behavior at the early signaling level, in spite of the similar inhibition of gonadotropin production.…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition and malnutrition lead to an increase in CRH levels, which can lead to a decrease in the release of GnRH and LH [18][19]. Decrease in GnRH and LH release lead to a decrease in reproductive function, including a decrease in fertility and an increase in the risk of miscarriage [20]. Leptin produced primarily in adipose tissue, acts on the hypothalamus to regulate appetite and energy balance.…”
Section: Nutrition and Its Effects On Reproductionmentioning
confidence: 99%
“…β-Catenin acts as a coactivator of SF-1 when it transduces Wnt signals to Dax1 [71], StarD1 [72], aromatase [73]; GnRH receptor [74], Müllerian inhibiting substance type II receptor [75], LHB/Lhb [76], and inhibin [77] target genes. Consistent with this, ChIP and site-directed mutagenesis assays have shown that activation of StarD7 expression requires the binding of β-catenin to the TCF4 transcription factor, suggesting that β-catenin functions as a bridge between SF-1 and TCF4 to form a ternary complex, which in turn activates StarD7 expression [66].…”
Section: Transcriptional Regulation Of Stard7mentioning
confidence: 99%